Go No-Go 555-timer / Amir Faisal Khamshah and Mohd. Rozimi Daud - Khamshah, Amir Faisal; Daud, Mohd. Rozimi (2003)
We are pleased to present a project that entitle Go No-Go 555 tester. We feel this project will be successful in introducing student the function of 555 timer and its operation, also the other ic’s which is flip-flop (74107) and NAND gate (7400). With considerable help from students and instructor, we are reconstructed the actual circuit to improve its functions. Our main goal are to increase student understanding of 555 timer tester, especially the components which in this circuit. In this project, we covered all components, discussing their characteristic and how the component operate, also operation of the circuit. We also include file of this circuit, which have drawn in electronic workbench software. So that we can learn all the waves and networking patterns where can be seen in practical work. Some waveforms have discussed in this report and the complete report of 555-timer tester is in report. Hardware, which had done, gives more description about this project. Design circuit on PCB, arranging component. The 555 timers is one of the most useful electronic devices in the market. Sometimes it is impossible to imaging our life without it. Signetics first introduced the 555 timers but today almost every semiconductor firm manufactures it. For this reason it is very cheap and broadly available. Here some peculiar uses of the 555 are going to be presentiment give more information about the circuit characteristic and more specific description.